INVESTIGATING THE ESSAY WRITING CHALLENGES EXPERIENCED BY STUDENTS AT BINA SARANA INFORMATIKA UNIVERSITY - Ahmad Bakhtiar (Universitas Indraprasta PGRI, 2023)
The study of writing has become an essential contributor to language learning research. Over the years, the existence of writing has led students to gain competence in learning a language. Throughout the process, students might have problems and experience errors that hinder them from producing the written product, especially an essay. Therefore, this study aims to critically identify and evaluate the students’ problems in writing essays, especially at Bina Sarana Informatika University. The research was conducted using a close-ended questionnaire with 37 questions regarding essay writing problems. Four significant problems: plagiarism, grammatical errors, lexical difficulties, and lack of planning became the focus of this study. Moreover, a lack of confidence also becames one of the problems in writing an essay. The finding of this research was that students agreed that lexical difficulties become the most common problem while writing an essay, with an average of 2,92. Interestingly, with an average of 2,3, the least common problem wass a grammatical error. By seeing the results from 21 respondents, it wass evident that the main thing that hinders students’ performance in writing an essay wass the difficulty in using the appropriate words and dictions based on context